2003
DOI: 10.1039/b207320j
|View full text |Cite
|
Sign up to set email alerts
|

Matrix-isolation FT-IR spectra and molecular orbital calculations on neutral N,N-dimethylglycine

Abstract: The structures and vibrational spectra of the preferred conformers of the neutral form of N,N-dimethylglycine (DMG) were studied by a combined approach, using DFT(B3LYP)/6-311++G** and MP2/6-31++G** calculations and low temperature matrix isolation IR spectroscopy. The conformational ground state was found to be the intramolecularly O-HÁ Á ÁN hydrogen-bonded GAT form, where the (lone pair)-N-C-C and N-C-C=O dihedral angles are 30 (gauche; G) and ca. 180 (anti; A), respectively, and the carboxylic group assumes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
61
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(68 citation statements)
references
References 34 publications
(63 reference statements)
6
61
1
Order By: Relevance
“…27,28 Most of these studies also reported theoretical calculations at various levels of theory. [5][6][7][8][9][10][11][12][13]15,17,[19][20][21][22][23][24][25][26][27][28] In general, the gas-phase results are qualitatively consistent with the matrix-isolation data, despite van der Waals forces appearing in the solid matrix between the sample and inner gas molecules. The most stable structures of aliphatic amino acids have been found to be stabilized by a bifurcated H-bond linking the carboxylic oxygen atom and the hydrogen atoms of the amino group.…”
Section: Introductionmentioning
confidence: 63%
See 4 more Smart Citations
“…27,28 Most of these studies also reported theoretical calculations at various levels of theory. [5][6][7][8][9][10][11][12][13]15,17,[19][20][21][22][23][24][25][26][27][28] In general, the gas-phase results are qualitatively consistent with the matrix-isolation data, despite van der Waals forces appearing in the solid matrix between the sample and inner gas molecules. The most stable structures of aliphatic amino acids have been found to be stabilized by a bifurcated H-bond linking the carboxylic oxygen atom and the hydrogen atoms of the amino group.…”
Section: Introductionmentioning
confidence: 63%
“…48 In matrixes, conformational cooling has been demonstrated to occur in glycine, sarcosine and other related R-substituted carbonyl compounds possessing barriers to intramolecular rotation of only a few kJ mol -1 . 15,19,49,50 Therefore, the conformational interconversion barriers between the relevant conformers of phenylalanine (in particular those conformers whose geometries differ essentially by the value of one torsion angle) were calculated to evaluate the possibility of this phenomenon to take place also in this molecule. The computed interconversion energy barriers are presented in Table 4.…”
Section: Energies and Abundances Of Phe Conformers And Conformationalmentioning
confidence: 99%
See 3 more Smart Citations